Synthesis and multiparametric evaluation of thiadiazoles and oxadiazoles as diacylglycerol acyltransferase type 1 inhibitors. Issue 1 (1st January 2016) - Mougenot, Patrick; Namane, Claudie; Fett, Eykmar; Goumy, Florence; Dadji-Faïhun, Rommel; Langot, Gwladys; Monseau, Catherine; Onofri, Bénédicte; Pacquet, François; Pascal, Cécile; Crespin, Olivier; Ben-Hassine, Majdi; et al.
Graphical abstract: Abstract: Chemical modulation of a formerly disclosed DGAT-1 inhibitor resulted in the identification of a compound with a suitable profile for preclinical development. Optimisation of solubility is discussed and a PK/PD study is presented.